EFEKTIFITAS PEMAHAMAN KONSEP IBADAH AGAMA ISLAM DENGAN MENYELENGGARAKAN KEGIATAN PESANTREN KILAT DI KELAS IV SDN 101821 PANCURBATU PADA SEMESTER 2 T.P.2018/2019 - Syahriani Tarigan (elt, 2020)
ABSTRACTThe problem of this research is:1.How are the end-of-year holiday activities, especially the expresscurricular activities of a short-term boarding school at SDN 101821 Pancurbatu in Semester 2T.P.2018/2019? 2. How is the correlation between extra-curricular a short-term Islamic boardingschool with student learning achievement, especially in the field of Islamic studies at SDN 101821Pancurbatu in Semester 2 T.P.2018/2019? 3. How is the relationship between the extra-curricularactivities of a short-term Islamic boarding school in the end-of-year holiday and the improvement oflearning achievements of grade IV students, especially in the field of Islamic studies at SDN101821 Pancurbatu in Semester 2 T.P.2018/2019? Objectives of Action Research:1.Explaining theholiday activities of the end of the school year ;2.Explaining the improvement of learningachievement, especially in the field of Islamic studies in grade 4 students at SDN 101821Pancurbatu in Semester 2 T.P.2018/2019.20 3. Obtaining data on the relationship between the endof-year holiday activities and the learning achievements of grade 4 students at SDN 101821Pancurbatu in Semester 2 T.P.2018/2019.This study used three rounds of action research. Eachround consists of four stages: design, activities and observations, reflections, and revisions. Dataobtained in the form of formative test results, observation sheets of teaching and learning activities.From the results of analysts obtained that the conclusions that can be drawn from this PTK are:1.Activities of grade 4 students of SDN 101821 Pancurbatu tend to increase with learning usingsimulation of a short-term Islamic boarding school activities 2.Cooperative skills of grade 4students of SDN 101821 Pancurbatu during the learning process using simulation of flash a shortterm boarding school activities can appear and most showed a significant increase in Islamiclearning achievements .3.Islamic learning achievements in grade 4 students at SDN 101821Pancurbatu experienced a significant increase after learning through learning using simulations of ashort-term boarding school activities It is recommended that the learning field of Islamic studies istimed to be replaced with innovative, learning techniques such as using simulated a short-termIslamic boarding school activities.Keywords: Islamic religious worship, a short-term Islamic boarding school